Lightning arrester aging rate due to contamination by soluble pollutants - Adnan, Sri Reski; Amali, Lanto; Mohamad, Yasin (International Journal of Mechanical Computational and Manufacturing Research, 2024)
The leakage current in the lightning arrester can be used as an indicator to determine the aging level of the arrester. Leakage current is influenced by contaminants in the arrester insulation. This research analyzes the effect of soluble contamination on the internal and external leakage current of lightning arresters as an indicator of arrester degradation. The contaminant used is NaCl (Sodium Chloride) which is dissolved in water, and a ZnO type lighting arrester to determine the level of NaCl contamination, the ESDD (Equivalent Salt Deposit Density) method is used. Lightning arresters that have been contaminated are measured for internal and external leakage currents flowing through the arrester insulation. Based on the experiments that have been carried out, the increase in leakage current in the internal lightning arrester for light, medium and heavy levels of contamination increases by an average of 30% for all test voltages. When compared with the international standard IEC 61643-1 which is determined at 1 mA, the internal leakage current value for light, medium and heavy pollution of the ZnO type Lightning arrester still meets the standard. However, if you use the PLN testing standard, namely 150 µA, the internal leakage current value for light, medium and heavy pollution of the ZnO type Lightning arrester does not meet the standard. Meanwhile, with low and medium contamination, there is no leakage current that occurs on the external part of the Lightning arrester. significant change